Inequalities in education from a global perspective: Theoretical approaches, dimensions and policy discussions - Margarita Langthaler; Julia Malik (Austrian Foundation for Development Research (ÖFSE), 2023)
Attention to the issue of inequalities in education has risen considerably after the COVID-19 pandemic. Research points to school dropout rates and learning losses that have risen disproportionately among weak socio-economic groups. While patterns are similar in most countries, the rise in educational inequalities and its socio-economic consequences are markedly wider in the Global South than in the Global North. Educational disparities in a North-South-dimension, however, predate the pandemic. Their roots go back to the colonial past and they are still firmly embedded in the global asymmetric division of labour, power and wealth. This Briefing Paper assesses the current international debate on inequality in education focussing on a North-South perspective. We will first briefly reflect on terminology before discussing theoretical approaches. Then, we will provide an overview of the current status quo of global disparities in education. Finally, we will analyse the international policy discussion.
Keywords: 330; education; inequalities; global disparities